دور المصالحة في حل الصراعات العربية الداخلية: نماذج مختارة - بيدر، زيد أحمد; علي، هند محمد عبدالجبار (جامعة تكريت - كلية العلوم السياسية, 2015)
The Arab region is living in difficult internal situations as a result of the political and security instability in some Arab countries, not only in the region, but also in the neighboring countries, although the results of these events are similar to chaos, internal strife and political instability. Including the internal causes of corruption, exclusion and tyranny. These events have resulted in a large number of deaths, injuries and disabilities, in addition to millions of displaced persons, and the destruction of the state's resources through the destruction of infrastructure and Facility and oil industry, and as a result of the conditions of negative realized most of the parties there is no way out of this crisis only through real and serum dialogue, not through violence, but must be done through the diagnosis of problems and the use of healthy ways to address them.
تعيش المنطقة العربية أوضاعاً داخلية صعبة نتيجة لعدم الاستقرار السياسي والأمني في بعض الدول العربية ولم تقتصر نتائجها على المنطقة فحسب بل امتدت إلى دول الجوار الإقليمي، وإن كانت نتائج هذه الأحداث متشابهة من فوضى واقتتال داخلي وعدم استقرار سياسي، الآن أسبابها كانت مختلفة، منها يرجع للتدخلات الدولية والإقليمية ومنها ما يرجع إلى أسباب داخلية ناتجة عن الفساد والإقصاء والاستبداد بالسلطة، خلفت هذه الاحداث نتائج أعداد كبيرة في عدد القتلى والجرحى والمعاقين، إضافة إلى ملايين المهاجريين، وتدمير مقدرات الدولة من خلال الدمار الذي لحق بالبنى التحتية والمنشأة النفطية والصناعية، ونتيجة للأوضاع السلبية أيقنت أغلب الأطراف أنه لا سبيل للخروج من هذه الأزمات إلا من خلال الحوار والمصالة الحقيقية، وليس من خلال العنف، وإنما يجب أن تتم عبر تشخيص المشاكل واستخدام وسائل صحية في معالجتها.
Keywords: الصراعات العربية العربية -- المصالحة السياسية -- الصراعات الداخلية -- الاستقرار السياسي -- التنمية الاقتصادية